Analysis of The Implementation of Criminal Sanctions for Employer Non-Compliance in Paying Contributions BPJS Health - Suhilman, Akhril Frambuniman; Budiono, Abdul Rachmad; Santoso, Budi (LPPM Universitas PGRI Sumatera Barat, 2025)
Health insurance is implemented with the aim of ensuring that participants receive health care benefits and protection to meet their basic health needs. However, many companies still violate Article 19 (1) or (2) of the BPJS Law, which states that companies have not complied with collecting, paying, and depositing premiums that are the responsibility of employees from their company to the Social Security Agency for Health (BPJS Kesehatan), resulting in many companies defaulting on BPJS Kesehatan insurance premiums and directly harming their employees who cannot utilize health insurance when they need health services. This study aims to analyze the application of criminal sanctions for companies non-compliance with BPJS Kesehatan insurance premium payments. The research method used is socio-legal empirical research. Employees who have not registered as BPJS participants and have never paid premiums cannot be categorized as participants. There are three conditions that lead to the imposition of criminal sanctions under Article 55 of the BPJS Law: (1) the company does not collect premiums that should be covered by the employees themselves; (2) the company have collected premiums that should be covered by employees, but the company didn’t deposit them to BPJS; (3) company do not pay and deposit premiums that are their responsibility to BPJS.